Lipid agonism: The PIP2 paradigm of ligand-gated ion channels - Hansen, Scott B. (Biochimica et biophysica acta, 2015)
The past decade, membrane signaling lipids emerged as major regulators of ion channel function. However, the molecular nature of lipid binding to ion channels remained poorly described due to a lack of structural information and assays to quantify and measure lipid binding in a membrane. How does a lipid–ligand bind to a membrane protein in the plasma membrane, and what does it mean for a lipid to activate or regulate an ion channel? How does lipid binding compare to activation by soluble neurotransmitter? And how does the cell control lipid agonism? This review focuses on lipids and their interactions with membrane proteins, in particular, ion channels. I discuss the intersection of membrane lipid biology and ion channel biophysics. A picture emerges of membrane lipids as bona fide agonists of ligand-gated ion channels. These freely diffusing signals reside in the plasma membrane, bind to the transmembrane domain of protein, and cause a conformational change that allosterically gates an ion channel. The system employs a catalog of diverse signaling lipids ultimately controlled by lipid enzymes and raft localization. I draw upon pharmacology, recent protein structure, and electrophysiological data to understand lipid regulation and define inward rectifying potassium channels (Kir) as a new class of PIP2 lipid-gated ion channels. [Display omitted] •Membrane resident lipids bind to and activate ion channels with ligand-like properties.•Inward rectifier potassium channel Kir2.2 is a PIP2 lipid-gated ion channel.•Lipid microdomains compartmentalize lipid signals.•Lipases and endocytosis terminate lipid signaling to ion channels.